Everyone loves a good story: Learning design in massive open online courses for language learning - De Caro-Barek, Veruska (Frontiers in Education, 2022)
These couple of years have witnessed an increase in the interest Higher Education Institutions (HEIs) have for Massive Open Online Courses (MOOCs). As the COVID19 situation amply showed us, MOOCs promptly became a practical way to secure continuity of education for students in lockdown. Educational Institutions chose the MOOC format to swiftly adapt to the "new normal" and deliver their courses online without incurring in too many unbudgeted expenses. However, the quality of teaching practices and learning design in MOOCs' Digital Learning Environments (DLE) varies considerably. By choosing a connectivist approach to understanding teaching and learning dynamics in digital learning environments, this article will elaborate on the importance of learning design and Digital Story Telling (DST) to create sustainable DLEs in MOOCs. To illustrate and support the logic threads of argumentation results from a mixed-methods (multi-modal) explanatory study of three international Language MOOCs developed by the Norwegian University of Science and Technology (NTNU) for FutureLearn (FL) will be presented and discussed.